Meaning of the Symbol of Gate of the Solo Palace Teaches Virtue - Muktiono, Ayub (International Journal of Science, Technology & Management, 2023)
The City of Solo (Surakarta) establishes itself as the City of Culture. The City of Solo as a City of Culture cannot be separated from the existence of the Solo Palace. The Solo Palace was built in 1755 by King Sunan Pakubuwono II with the palace area which eventually developed into the City of Solo. The Solo Palace area can be seen through the signs of the existence of the gate in several places. The gate is not only a sign of the boundaries of the palace territory, but the gate has cultural messages, behavior, strata levels and in the form of the gate itself it is loaded with messages of meaning as a communication of the king's policies with his people. This research is an interpretation research with a semiological approach using Barthes' theory. Interpretation is done by cultural contextual correlation. This semiological approach with contextual correlation of community culture is termed by the author as an ethnosemiological study. The results of the interpretation of the forms at the gate of the Solo Palace show that these forms contain very wise meanings and messages and are teachings of virtue, messages of governance and leadership of power. Messages through the symbols of shapes at the gates of the Solo Palace have existed since the mid-17th century, while the development of semiology theory only occurred in the 19th century. This proves that the Solo Palace Founders had implemented semiology theory before the theory was born. The results of the interpretation of the forms at the gate of the Solo Palace show that these forms contain very wise meanings and messages and are teachings of virtue, messages of governance and leadership of power. Messages through the symbols of shapes at the gates of the Solo Palace have existed since the mid-17th century, while the development of semiology theory only occurred in the 19th century. This proves that the Solo Palace Founders had implemented semiology theory before the theory was born. The results of the interpretation of the forms at the gate of the Solo Palace show that these forms contain very wise meanings and messages and are teachings of virtue, messages of governance and leadership of power. Messages through the symbols of shapes at the gates of the Solo Palace have existed since the mid-17th century, while the development of semiology theory only occurred in the 19th century. This proves that the Solo Palace Founders had implemented semiology theory before the theory was born.